Comparison of the bioactivity and apoptotic responses of hyaline cartilage chondrocytes and fibrocartilage chondrocytes obtained by bone marrow stimulation in rats - Hakan Cicek; Umit Tuhanioglu; Figen Cicek (Acta Orthopaedica et Traumatologica Turcica)
Objective: The microfracture technique is often considered the standard therapy for treating cartilage defects. The aim of the treatment is the migration of mesenchymal stem cells from the bone marrow into the defect area. However, this regeneration process often results in the formation of fibrocartilage instead of natural hyaline cartilage, due to cellular mechanisms whose causes are not well understood. Therefore, in this study, the differences in bioactivity and apoptosis of fibrocartilage tissue-derived chondrocytes (FCh) obtained by bone marrow stimulation and natural hyaline cartilage tissue-derived chondrocytes (HCh) in the knee joint of rats were compared.